No quick fixes: four interacting constraints to advancing agroecology in Uganda. Issue 4 (1st October 2016) - Isgren, Ellinor
Abstract : A century after its inception, agroecology has entered mainstream development debates as a more sustainable alternative to conventional agricultural modernization of relevance not least for improving smallholder agriculture in sub-Saharan Africa. Agroecology is a broad concept considered to have transformative potential, yet as a research field it has often been technology-centred and focused at the local level. Building on the experiences of Ugandan agroecologists working in an array of agricultural professions throughout the country, this paper identifies and discusses major barriers to agroecology in Uganda. Inductive analysis of qualitative data from interviews and focus groups generated four types of interacting barriers; constraints at farmer level, an agricultural knowledge system favouring conventional approaches, adverse and intertwined political and economic interests, and cross-cutting ideological and discursive pressures. These broad challenges become manifest in the accounts presented, making clear that barriers to and therefore also appropriate strategies for advancing agroecology must be treated as contextual even if a 'global movement' is emerging around it. The discussion suggests theoretical lenses for further inquiry into agroecology and its realization in light of these constraints.